Diet and exercise interventions for individuals at risk for type 2 diabetes: a scoping review protocol. Issue 11 (17th November 2020) - MacPherson, Megan; Cranston, Kaela; Locke, Sean; Vis-Dunbar, Mathew; Jung, Mary E
Abstract : Introduction: Global rates of type 2 diabetes (T2D) are on the rise and there is a need for both effective and replicable interventions to decrease this incidence. Systematic reviews highlight the efficacy of diet and exercise interventions in decreasing T2D risk; however, no review to date provides clear information regarding intervention details (eg, what is delivered, by whom, to whom, when, and mode of delivery). This paper outlines the protocol for a scoping review summarising intervention characteristics of diet and exercise programmes for individuals at risk for T2D. From the included studies and through the use of the Template for Intervention Description and Replication (TIDieR), the scoping review that results from this protocol paper will provide a narrative analysis of how diabetes prevention programmes are being reported and implemented. Methods: A comprehensive search strategy is outlined to identify studies within Medline, CINAHL, PsycINFO, EMBASE and SPORTDiscus. The search strategy will include terms relating to diet and exercise interventions and diabetes risk. To determine eligible studies, predefined inclusion and exclusion criteria will be used independently by two review authors. To be included, studies must be delivering a diet and/or exercise intervention among adults who have been identified as at risk for developing T2D with an outcome related to diabetes prevention. Data extraction of those studies that meet inclusion criteria will be guided by the TIDieR). Ethics and dissemination: Ethical approval is not required as this review will be using previously collected data. Review findings will be presented at scientific conferences and published in a peer-reviewed journal.